Mouse podoplanin supports adhesion and aggregation of platelets under arterial shear: A novel mechanism of haemostasis. (3rd October 2018) - Lombard, Stephanie E.; Pollitt, Alice Y.; Hughes, Craig E.; Di, Ying; Mckinnon, Tom; O'callaghan, Chris A.; Watson, Steve P.
Abstract: The podoplanin-CLEC-2 axis is critical in mice for prevention of hemorrhage in the cerebral vasculature during mid-gestation. This raises the question as to how platelets are captured by podoplanin on neuroepithelial cells in a high shear environment. In this study, we demonstrate that mouse platelets form stable aggregates on mouse podoplanin at arterial shear through a CLEC-2 and Src kinase-dependent pathway. Adhesion and aggregation are also dependent on the platelet glycoprotein (GP) receptors, integrin αIIbβ3 and GPIb, and the feedback agonists ADP and thromboxane A2 (TxA2 ). CLEC-2 does not bind to von Willebrand factor (VWF) suggesting that the interaction with podoplanin is sufficient to both tether and activate platelets. Consistent with this, the surface plasmon resonance measurements reveal that mouse CLEC-2 binds to mouse podoplanin with nanomolar affinity. The present findings demonstrate a novel pathway of hemostasis in which podoplanin supports platelet capture and activation at arteriolar rates of shear.